CMA Whaleboat Crew Will Race - Vallejo Times-Herald (Vallejo Times-Herald)
A squad of oarsmen will represent California Maritime Academy Saturday in the annual Whaleboat races on the Maritime Day program at San Francisco Aquatic Park.